Grassing techniques for surface stabilisation of platinum tailings dams in South Africa - van Wyk, SJ; van Deventer, PW; Smit, PJL (Mine Closure 2009: Proceedings of the Fourth International Conference on Mine Closure, 2009)
The aim of this study is to determine cost-effective grassing methods to stabilise the side slope surfaces of platinum tailings dams. Eight dry-land treatments were implemented and analysed after one year to determine the minimum fertility requirements to establish a self-regenerating grass cover; to identify native pasture grass species that would survive and facilitate bio-system development; and to quantify plant production for possible post-mining rehabilitation purposes. Treatment plots of 150 m2 were treated with composted materials, inorganic fertilisers, grass, and branch mulch and rock rip-rap and replicated in triplicate. Treatment plots were analysed for soil chemical status, plant species reflectance and abundance, plant production and plant tissue elemental concentrations. The data after one growing season revealed that all treatments had production rates of more than 350 g m-2 dry mass, with higher production on the compost treatments. Crown cover exceeded 80 per cent on all plots and the highest basal cover was found to be on the grass-mulch treated plots. Rhodes (Chloris gayana (Kunth)) dominated the species frequency with noticeable occurrence of Buffalo grass (Cenchrus ciliaris (L.)). Treatments that presented surface roughness and the best safe-site conditions with presumably improved moisture retention, presented the best establishment results. It was found that pH, electrical conductivity (EC) and exchangeable sodium percentage (ESP) values of platinum tailings material were the primary indicators for vegetation performance. Concentrations of arsenic (As), molybdenum (Mo), selenium (Se), vanadium (V), chromium (Cr) and iron (Fe) found in the grass leaf tissue were higher than those reported in the literature for animal- safe forage, which renders grazing unsuitable as a land use option. Future studies should focus on refinement of the quantities and types of composted material to be applied, the effect of leaching on soil nutrient cycling, monitoring of soil and vegetation dynamics on the treated platinum tailings and land use options for the revegetated platinum tailings material.